Fat body cells of Amblyomma cajennense partially engorged females (Acari: Ixodidae) and their role on vitellogenesis process - Denardi, Sandra Eloisi [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
During the process of Arthropoda reproduction, the synthesis and uptake of proteins, carbohydrates, and lipids by oocytes is termed vitellogenesis. These compounds that will make up the yolk may be in ticks endogenously synthesized by the oocytes and/or exogenously produced by the fat body and pedicel cells. This study examined the fat body of Amblyomma cajennense ticks at the cytochemical ultrastructural level to demonstrate the presence of lipids, proteins and carbohydrates in trophocytes. The lipids were detected in higher quantity than proteins and carbohydrates in the fat body cells, suggesting that the role of the fat body in tick is stored lipids and carbohydrates to convert them in energy, or still they could be used with cell structural purpose. The electrophoresis technique applied at A. cajennense fat body demonstrated specifically the molecular mass of proteins: about 98 kDa. By the other hands, the fat body is not the organ responsible for the synthesis of the yolk protein, role probably performed by the pedicel cells. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Amblyomma cajennense; Fat body; Ovary; Tick; Vitellogenesis